Pengembangan E-LKPD Berbasis Socio-Scientific Issues (SSI) Menggunakan Live work sheets Pada Materi Kesetimbangan Kimia Kelas XI SMA/MA Sederajat - Nur Latiffahni; Rasmiwetti; Sri Haryati (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to develop E-LKPD based on socio-scientific issues (SSI) using liveworksheets on chemical equilibrium material for grade XI SMA/MA equivalent, to determine the validity of E-LKPD based on aspects of content feasibility, characteristics of Socio-scientific Issues, presentation, language, appearance, and software utilization and to determine user responses to the developed E-LKPD. This study was designed using a research and development design R&D (Research and Development) using the ADDIE model consisting of five stages of the ADDIE model consisting of Analysis, Design, Development, Implementation and Evaluation. However, this study was only conducted up to the Development stage. The instruments used were validation sheets and user response questionnaires. Validation was carried out by two material expert validators and one media expert validator, as well as user responses obtained from teachers and students. After validation was carried out twice, the results of the expert validation of the material on the aspects of content feasibility, characteristics of Socio-Scientific Issues, presentation, and language were respectively 93.75%, 90.625%, 87.50%, and 87.50% with valid criteria. The results of media validation on the aspects of appearance, and software utilization were 100% and 100% with valid criteria. The results of the user response test obtained a score of 96.66% by chemistry teachers with very good criteria and 95.77% by students with very good criteria.